Pemodelan Bangunan Untuk Simulasi Respons Struktur Akibat Beban Dinamik - Sukoyo Sukoyo (Politeknik Negeri Semarang, 2012)
The response structure due to dynamic load or earthquake in a building is very important to be know.Therefore we tried to do some research with make a model that can show the behavior of structure when receives the dynamic load. In this research the structure is modeled with two-dimensional discrete system with a system of beams and columns of the same strength, it is easier to see the behavior of structure. The system is made by Power Fortran language program Station. The methods used for solve structural vibration dynamical equations is the Runge-Kutta order 4. The results shown in graphical form with the help of MS Excel program. From the graph shows that the pattern of responses produced is same with a given load pattern but have different intensity and deviation. Beside that , the structure will receives displacement, velocity, and acceleration are greater when receiving a load that is not harmonious with the same frequency. This suggests that the structure would be more resistant to a greater load if given regularly, compared with the sudden load.